2005
DOI: 10.1007/s10096-005-1373-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of bacterial stool cultures and viral antigen tests based on clinical manifestations of acute gastroenteritis in pediatric patients

Abstract: The study presented here aimed to elucidate the diagnostic value of bacterial stool cultures and viral antigen tests when performed based on the clinical characteristics of acute gastroenteritis in infants and young children. A total of 21 (11.2%) bacterial and 74 (39.6%) viral infections affecting 187 children under the age of 3 years was investigated. Blood (p<0.001) and mucus (p=0.014) in the stool and a C-reactive protein (CRP) level of >or=50 mg/l (p=0.006) were more significantly associated with gastroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
6
1
6
Order By: Relevance
“…Presence of fever is one of the most important clinical findings affecting the clinician's decision in the approach to the infectious diseases. In the clinical studies, it has been reported that fever is observed more frequently in rotavirus gastroenteritis compared to the other viral agents [14,18,25-27]. We did not find any difference regarding fever between the rotavirus cases and the rotavirus-negative cases in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Presence of fever is one of the most important clinical findings affecting the clinician's decision in the approach to the infectious diseases. In the clinical studies, it has been reported that fever is observed more frequently in rotavirus gastroenteritis compared to the other viral agents [14,18,25-27]. We did not find any difference regarding fever between the rotavirus cases and the rotavirus-negative cases in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Infectious diarrhea was defined as one of abnormal laboratory findings; a positive bacteria culture from stools or leukocytosis (≥15,000/mm 3 ) in peripheral blood or a C-reactive protein level of ≥5 mg/dL, and an improvement on antibiotics10). Lactose intolerance was defined as a fecal pH lower than 5.0, a resolution of symptoms on a 2-week strict lactose-free diet and the recurrence of symptoms after reintroducing dairy foods, all in the absence of any evidence of infection11).…”
Section: Methodsmentioning
confidence: 99%
“…Клиническая симптоматика бактериального гастро-энтерита в совокупности с высоким уровнем лейкоцитов в кале позволяет уверенно судить о наличии бактериаль-ной инфекции (чувствительность 74%, специфичность 94%) [34]. На практике, основываясь только на клиниче-ской симптоматике и микроскопии кала, дифференциро-вать бактериальные и вирусные гастроэнтериты удается не всегда.…”
Section: пкт при остром тонзиллитеunclassified